Comparative Analysis of Intellectual Quotient in Developmental Population with Severe Hearing Loss: Hearing Aids vs. Cochlear Implant Users - Arianna Di Stadio; Pietro De Luca; Valentina Ippolito; Paola Vedova; Sabina Garofalo; Rosaria Turchetta; Salvatore Ferlito; Antonio della Volpe (Life, 2023)
The development of language, memory and intellectual functions is linked to normal hearing and correct sounds interpretation. Hearing loss (HL), especially in its severe form, negatively affects the development of these functions. This prospective study aimed at comparing the Intelligent Quotients (IQ) of children with cochlear implants (CI) with the ones of people wearing hearing aids (HA) after one year of hearing rehabilitation. 21 subjects with severe/profound bilateral hearing loss (deafness) were included in this study. Eleven children with congenital profound HL underwent CI and ten children with moderate to severe HL (congenital and acquired) were rehabilitated by HA. Children’s IQs were assessed at enrolment (T0) and 12 months after hearing aids/CI use plus speech therapy. Statistical analyses were performed to analyze the data within and between groups. Comparison of IQs showed no statistically significant differences between CI and HA none at T0 and T1. The subtests showed lower scores in verbal comprehension and process speed index in patients treated with HA when compared to CI. This study showed that auditory rehabilitation can support the normal development of cognitive function in children between six and eight years of age. The use of the correct hearing aids based on the patient’s hearing thresholds is important to maximize the rehabilitation outcomes. Due to the small sample size, although stratified for age, our results must be considered preliminary and further analyses on larger samples are needed to confirm our data.